A method of estimating residual stresses from hardness distributions in view of the fatigue strength of carburized gear teeth. (5th August 2014) - Tobe, T.; Kato, M.; Inoue, K.
For the purpose of reliable design of vehicle gears, this paper deals with a method of calculating residual stress and the effectiveness on fatigue strength of carburized spur gears. In general, residual stresses are caused by the time lag of the transformations, the differences in thermal shrinkages and the differences in volume expansion of structures between the case and the core. In this paper, the last cause is considered to be the most significant and practically important for carburized gears. The calculation is, therefore, based on the volume difference between case and core due to the martensitic transformation in cooling. The two–dimensional FEM is used for the calculation.